2010
DOI: 10.1523/jneurosci.2234-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Agrp Neurons Mediate Sirt1's Action on the Melanocortin System and Energy Balance: Roles for Sirt1 in Neuronal Firing and Synaptic Plasticity

Abstract: Sirt1 has been associated with various effects of calorie restriction, including an increase in lifespan. Here we show in mice that a central regulatory component in energy metabolism, the hypothalamic melanocortin system, is affected by Sirt1, which promotes the activity and connectivity of this system resulting in negative energy balance. In adult mice, the pharmacological inhibition of brain Sirt1 activity decreased Agrp neuronal activity and the inhibitory tone on the anorexigenic POMC neurons, as measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
193
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 56 publications
10
193
2
2
Order By: Relevance
“…Our data support the notion that the CNS can affect immune functions (40,41), which can supersede the predicted effects of circulating metabolic hormones, such as leptin. These results, together with our recent demonstration of specific behavioral and metabolic phenotypes of AgRP-Sirt1 KO animals (3,4), suggest that traits of altered motivated behaviors and basic metabolic parameters can be predictors of adaptive immune system phenotypes.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Our data support the notion that the CNS can affect immune functions (40,41), which can supersede the predicted effects of circulating metabolic hormones, such as leptin. These results, together with our recent demonstration of specific behavioral and metabolic phenotypes of AgRP-Sirt1 KO animals (3,4), suggest that traits of altered motivated behaviors and basic metabolic parameters can be predictors of adaptive immune system phenotypes.…”
Section: Discussionmentioning
confidence: 57%
“…We used the knockdown model of Sirt1 in the NPY/AgRP neurons previously described (4). Briefly, we used Cre/Lox technology to knock down the catalytic domain of Sirt1 in this population of cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SIRT1 is expressed in the orexigenic neuropeptide Y (NPY)/Agouti-related peptide (AGRP) and anorexigenic proopiomelanocortin (POMC) neurons, which are major components in regulating feeding and energy expenditure in the arcuate nucleus of the hypothalamus (Sasaki and Kitamura, 2010). Several studies in mice and rats reported that SIRT1 regulates food intake and body weight by acting on the NPY/AGRP and POMC neurons (Cakir et al, 2009;Dietrich et al, 2010). …”
Section: Sirt1mentioning
confidence: 99%